G-MXene-PAA-Fe < 3 + > hydrogel as well as preparation method and application thereof

By modifying the combination of MXene with acrylic acid and Fe3+, G-MXene-PAA-Fe3+ hydrogel with excellent self-healing, mechanical and electrical conductivity was prepared, which solved the problem of easy oxidation of traditional hydrogels and MXene, and improved the Its application potential in the fields of biomedical and sensors.

CN119219814AActive Publication Date: 2024-12-31CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411555095.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-31
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The application of traditional hydrogels in biomedical and sensor fields is limited by their poor self-healing performance, low conductivity, poor mechanical properties, poor biocompatibility and slow response to external stimuli. The MXene conductive hydrogels are easy to Oxidation leads to structural decomposition, affecting its application stability.

Method used

The modified transition metal carbon/nitride MXene and acrylic radical polymerization and metal coordination bond hydrogel system was used to prepare G-MXene-PAA-Fe3+ self-healing conductive hydrogel by one pot method, using L-ascorbic acid anti- The oxidant modifies MXene, enhances its oxidative stability and conductivity, and forms a stable hydrogel network through the cross-linking of Fe3+ and PAA chains.

Benefits of technology

The excellent stability, self-healing performance, mechanical properties and conductive properties of G-MXene-PAA-Fe3+ hydrogel are achieved, which improves its application prospects in the field of flexible sensors and significantly extends the oxidative stability of MXene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219814A_ABST
    Figure CN119219814A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biosensing, and particularly relates to G-MXene-PAA-Fe < 3 + > hydrogel as well as a preparation method and application thereof. The preparation method comprises the following steps: modifying MXene by adopting an antioxidant to prepare modified G-MXene; then, acrylic acid (AA) free radical polymerization chemical crosslinking is used as a first network, polyacrylic acid (PAA)-Fe < 3 + > metal ion complexing is used as a second network, modified G-MXene is used as a cross-linking agent and a conductive nano filler, and under the action of an initiator ammonium persulfate, the G-MXene-PAA-Fe < 3 + > self-healing conductive hydrogel is prepared by adopting a simple and easy-to-operate one-pot method. The prepared self-healing conductive hydrogel has excellent stability, self-healing performance, mechanical performance, conductivity and sensing performance, and has a wide application prospect in the field of flexible sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biosensor technology and specifically relates to a G-MXene-PAA-Fe 3+ Hydrogel and its preparation method and application. Background Art

[0002] Hydrogel is a flexible and pliable polymer material with a 3D network structure, containing a large number of hydrophilic groups. It can absorb dozens or even hundreds of times more water or liquid than itself, and can swell without being soluble in water, so it has a good water retention capacity. As a special type of hydrogel, smart hydrogel integrates sensing, driving and information processing, has intelligent characteristics, and has broad application prospects in traditional biomedicine and sensing fields. However, traditional hydrogels still have shortcomings such as poor self-healing performance, low conductivity, poor mechanical properties, poor biocompatibility, slow response to external stimuli, and single response, which limits their further application in the field of sensing. Therefore, it is necessary to further improve the performance of hydrogels and expand their application in flexible sensors.

[0003] Studies have shown that introducing functional nanomaterials into hydrogel networks can improve their conductivity, mechanical properties, and biocompatibility, and bring them new functional responsiveness, thus breaking the limitations of traditional hydrogel technology. Among all two-dimensional nanomaterials, MXene is a type of transition metal carbon / nitride two-dimensional nanomaterial with a graphene-like structure. Its chemical formula is M n+1 X n T X (n=1-4), where M represents an early transition metal (Ti, V, Nb, etc.), X represents C or N, T X Represents different surface terminal groups (-OH, -O, -F, etc.). MXene is widely used in electrochemical energy storage conversion, electromagnetic interference shielding, sensing, biomedicine and other fields due to its excellent properties such as conductivity, hydrophilicity, processability, specific surface area and mechanical strength. For example, inspired by the ordered structure of muscles, the research team of Jilin University prepared anisotropic MXene conductive hydrogels by directional freezing method. Due to the anisotropy of MXene conductive hydrogels, their mechanical properties and conductivity are enhanced in specific directions. Through solvent replacement, the hydrogel has a wide temperature resistance range of -36°C to 25°C. The MXene conductive hydrogel can be used as a wearable flexible sensor and 3D sensing array. However, when MXene is exposed to air or water, it will rapidly oxidize and degrade within a few days, leading to the decomposition of the layered, two-dimensional structure to form titanium dioxide (TiO 2 ) and carbon (C). The oxidation stability and surface self-weight stacking problems of MXene seriously hinder its application in practical industry.

[0004] In addition, due to the inherent low Young's modulus of hydrogels and the complex load-bearing and dynamic environment in the human body, hydrogel bioelectronic devices are easily damaged during use. In order to extend their durability, reliability and service life, giving hydrogels self-healing properties is a better choice. However, in order to prepare hydrogels with excellent self-healing properties, conductive properties, mechanical properties, sensing properties and other functions, there are still many challenges to overcome in terms of raw material selection, preparation process, and practical application. Summary of the invention

[0005] In view of this, the present invention proposes a self-healing conductive hydrogel that can be applied to wearable flexible sensors and its preparation method and application. Based on the new transition metal carbon / nitride MXene, the present invention introduces the antioxidant modified MXene into the acrylic acid free radical polymerization and metal coordination bond hydrogel system, and prepares MXene-PAA-Fe by a simple one-pot method. 3+ Self-healing conductive hydrogel, which has excellent stability, self-healing properties, mechanical properties, conductive properties and sensing properties, and can be used in the field of flexible sensors.

[0006] One of the purposes of the present invention is to provide a method for preparing G-MXene-PAA-Fe 3+ Compositions of self-healing conductive hydrogels.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] For the preparation of G-MXene-PAA-Fe 3+ A composition of a self-healing conductive hydrogel, the composition comprising the following components: modified G-MXene, acrylic acid and FeCl 3 ; The volume ratio of the modified G-MXene to the acrylic acid is 170-180:230-270; the FeCl 3 The volume of the acrylic acid monomer is 2 to 4 mol%.

[0009] Preferably, the volume ratio of the modified G-MXene to the acrylic acid is 175:250.

[0010] Furthermore, the MXene is modified by an antioxidant to obtain the modified G-MXene; the volume ratio of the MXene to the antioxidant is 1:5-10; and the antioxidant is L-ascorbic acid.

[0011] Considering the disadvantage of MXene being easily oxidized, the present invention uses L-ascorbic acid (VC) to modify it with antioxidant to obtain G-MXene. Antioxidant treatment significantly changes the surface chemistry of MXene and removes a large number of F groups on the surface of MXene. In the presence of antioxidant, Ti + To Ti 2+ / Ti 3+ The chemical state transformation of Ti is inhibited; 4+ The increase with time is slow. Compared with the unmodified MXene nanosheets, the conductivity of the modified G-MXene is not significantly reduced, and the morphology still maintains a certain stability after 22 days.

[0012] Furthermore, the composition also contains an initiator; the volume ratio of the acrylic acid to the initiator is 4 to 6:1; and the initiator is ammonium persulfate.

[0013] Preferably, the volume ratio of the acrylic acid to the initiator is 5:1.

[0014] The second object of the present invention is to provide a method for preparing G-MXene-PAA-Fe based on the above composition. 3+ The method for preparing self-healing conductive hydrogel adopts a simple one-pot method and can prepare the self-healing conductive hydrogel in one container.

[0015] To achieve the above object, the present invention adopts the following technical solutions:

[0016] Preparation of G-MXene-PAA-Fe based on the above composition 3+ The method for self-healing conductive hydrogel comprises the following steps:

[0017] S1: under the action of ultrasound, deionized water, modified G-MXene, acrylic acid monomer and ammonium persulfate solution are added in sequence to uniformly disperse to obtain G-MXene-PAA hydrogel; the volume ratio of the deionized water, the modified G-MXene, the acrylic acid monomer and the ammonium persulfate solution is 500:170-180:230-270:50;

[0018] S2: The G-MXene-PAA hydrogel obtained in S1 was placed in FeCl 3 Soak in the solution to obtain G-MXene-PAA-Fe 3+ Self-healing conductive hydrogels.

[0019] Furthermore, in S1, the volume ratio of the deionized water, the modified G-MXene, the acrylic acid monomer and the ammonium persulfate solution is 10:3.5:5:1.

[0020] Furthermore, in S1, the concentration of the modified G-MXene is 10 mg / mL; and the concentration of the ammonium persulfate solution is 50 mg / mL.

[0021] Further, in S2, the FeCl 3 The amount of the solution is 2-4 mol %, preferably 3 mol %, of the acrylic acid monomer.

[0022] Further, in S2, the FeCl 3 The concentration of the solution was 15 mg / mL.

[0023] Further, in S2, the soaking time is 25-60 minutes, preferably 30 minutes.

[0024] Further, the preparation method of the modified G-MXene is as follows:

[0025] (1) Ti 3 AlC 2 Add it to LiF / HCl etching solution to synthesize MXene by selective etching method;

[0026] (2) Using an antioxidant to modify the MXene obtained in step (1) to obtain the modified G-MXene.

[0027] Furthermore, the MXene obtained in step (1) is a two-dimensional single-layer flake structure with a thickness of about 3.0-3.5 nm and a lateral size of about 1.3-1.7 μm.

[0028] Furthermore, the LiF / HCl etching solution is prepared by dissolving LiF in a 9M HCl solution at room temperature and magnetically stirring for 20 minutes to obtain an etching solution; the ratio of the LiF to the 9M HCl solution is 1 g:20 mL.

[0029] Furthermore, step (1) is specifically as follows:

[0030] Ti 3 AlC 2 Slowly add it to the etching solution, stir at 35°C for 24 hours, centrifuge at 3500 rpm for 5 minutes, discard the supernatant and use 1M hydrochloric acid and deionized water for multiple centrifugal washing until the pH of the supernatant is greater than 5; discard the supernatant and continue to add water, ultrasonicate the solution in an ice bath under nitrogen for 1 hour, centrifuge for 1 hour, and collect the supernatant to prepare a single-layer MXene suspension.

[0031] Furthermore, the reaction conditions in step (2) include: ultrasound for 4-10 minutes, and oscillation reaction for 4-10 hours; preferably, ultrasound for 5 minutes, and oscillation reaction for 5 hours.

[0032] Furthermore, in step (2), the volume ratio of the MXene to the antioxidant is 1:5 to 10, preferably 1:7; and the antioxidant is L-ascorbic acid.

[0033] Furthermore, in step (2), the reaction conditions are ultrasound for 4-6 min and shaking on a shaking table for 4-8 h, and most preferably ultrasound for 5 min and shaking on a shaking table for 5 h.

[0034] In the present invention, G-MXene-PAA-Fe 3+ The principle of the self-healing conductive hydrogel is as follows: First, L-ascorbic acid is used as an antioxidant to modify MXene nanosheets to prepare long-term stable modified G-MXene nanosheets. Then, in the presence of modified G-MXene nanosheets (as a crosslinker and conductive nanofiller) and initiator ammonium persulfate, G-MXene-PAA hydrogel is formed by in-situ free radical polymerization of acrylic acid monomers. Finally, Fe 3+ As the coordination center, the polarized groups on the modified G-MXene nanosheets are coordinated and cross-linked with the carboxyl groups in the PAA chains to form G-MXene-PAA-Fe 3+ Hydrogel.

[0035] The third object of the present invention is to provide a G-MXene-PAA-Fe prepared by the above-mentioned preparation method. 3+ Self-healing conductive hydrogels.

[0036] To achieve the above object, the present invention adopts the following technical solutions:

[0037] G-MXene-PAA-Fe prepared by the above preparation method 3+ Self-healing conductive hydrogels.

[0038] Furthermore, in the self-healing conductive hydrogel, acrylic acid free radical polymerization chemical cross-linking forms a first network, polyacrylic acid (PAA)-Fe 3+ Metal ion complexation forms the second network.

[0039] Furthermore, the G-MXene-PAA-Fe 3+ The self-healing time of the self-healing conductive hydrogel is 15 minutes to 12 hours, and the self-healing rate is 92% to 98%.

[0040] The fourth object of the present invention is to provide a composition and / or the G-MXene-PAA-Fe 3+ Application of self-healing conductive hydrogels in the preparation of wearable flexible sensors.

[0041] The beneficial effects of the present invention are:

[0042] 1. The present invention uses L-ascorbic acid as an antioxidant to modify MXene nanosheets to prepare long-term stable MXene nanosheets (G-MXene nanosheets). G-MXene has a conductivity 3.5 times higher than MXene and better oxidation stability. The G-MXene nanosheet can play a variety of roles in the gelation process. The synergy between it and other elements in the hydrogel network will lead to better stability of the hydrogel, and has good application prospects in hydrogel flexible sensors.

[0043] 2. The present invention uses acrylic acid monomer, FeCl under the action of initiator ammonium persulfate. 3 and modified G-MXene nanosheets to obtain MXene-PAA-Fe by a simple one-pot method 3+ Self-healing conductive hydrogel. MXene nanosheets, as a multifunctional crosslinker, work together with the initiator ammonium persulfate to effectively promote the free radical polymerization of AA monomer within 10 minutes, while giving the hydrogel conductivity, it also avoids the high temperature and long time required for the traditional AA monomer free radical polymerization.

[0044] 3. The present invention is in PAA-Fe 3+ The introduction of G-MXene nanosheets into the system effectively improves its mechanical properties and electrical conductivity. 3+ The tensile strength of the hydrogel can reach 1443.8 kPa, the elongation at break can reach 926.7%, and the conductivity can reach 2.8 S·m -1 ; When modified G-MXene:AA:APS:H 2 When O=3.5:5:1:10 (i.e., in the reaction system, the amount of modified G-MXene is 175 μL, the amount of acrylic acid monomer is 250 μL, the amount of ammonium persulfate solution is 50 μL, and the amount of water is 500 μL), the G-MXene-PAA-Fe prepared by the present invention 3+ Self-healing conductive hydrogel has the best comprehensive performance.

[0045] 4. G-MXene-PAA-Fe of the present invention 3+ The self-healing conductive hydrogel has good self-healing properties with a self-healing rate of 94.2%.

[0046] 5. G-MXene-PAA-Fe of the present invention 3+ When used in sensors, self-healing conductive hydrogels can well feedback the real-time relative resistance changes under different actions, and have good application prospects as wearable intelligent strain sensors with a strain sensitivity of up to 3.68.

[0047] 6. The present invention further explores G-MXene-PAA-Fe 3+ Effects of hydrogel preparation conditions on various properties (conductivity, mechanical properties, self-healing, etc.). The final prepared G-MXene-PAA-Fe 3+ The hydrogel has excellent self-healing properties, electrical conductivity, mechanical properties, sensing properties, biocompatibility and oxidative stability, and has good application prospects in the field of sensing. At the same time, the present invention also provides a reference for the application and preparation of MXene-based conductive hydrogels in flexible sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Schematic diagram of the synthesis of MXene nanosheets;

[0049] Figure 2 For MXene-PAA and MXene-PAA-Fe 3+ Schematic diagram of the preparation process of hydrogel;

[0050] Figure 3 This is a diagram of the light visual observation results of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL, where: Figure 3 -A is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL at day 0; Figure 3 -B is a graph of MXene and G-MXene dispersions at a concentration of 1.25 mg / mL at 3 days; Figure 3 -C is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL at 5 days; Figure 3 -D is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL at 8 days; Figure 3 -E is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL at 14 days after shaking; Figure 3 -F is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL after shaking under sunlight for 14 days; Figure 3 -G is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL at 22 days; Figure 3 -H is a graph of MXene and G-MXene dispersions with a concentration of 1.25 mg / mL at 22 days after shaking;

[0051] Figure 4 This is a diagram of the light visual observation results of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL, where: Figure 4 -A is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 0 day; Figure 4 -B is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 3 days; Figure 4 -C is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 5 days; Figure 4 -D is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 8 days; Figure 4 -E is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 14 days after shaking; Figure 4 -F is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL 14 days after shaking under sunlight; Figure 4 -G is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 22 days; Figure 4 -H is a graph of MXene and G-MXene dispersions with a concentration of 0.5 mg / mL at 22 days after shaking;

[0052] Figure 5 The XPS spectra of MAX, MXene and G-MXene and the high-resolution spectrum of Ti2p are shown below. Figure 5 -A is the XPS spectra of MAX, MXene and G-MXene; Figure 5 -B is the high-resolution spectra of Ti2p of MAX, MXene and G-MXene;

[0053] Figure 6 The mixed solution of AA, APS and deionized water, and the gelation diagram of MXene-PAA hydrogel within 10 minutes, where: Figure 6 -A and B are the initial states of the mixed solution of AA, APS and deionized water; Figure 6 -C and D are the states of the mixed solution of AA, APS and deionized water after mixing for 10 min; Figure 6 -E and F are the initial states of the mixed solutions of AA, APS and MXene; Figure 6 -G and H are the states of the mixed solution of AA, APS and MXene after mixing for 10 min;

[0054] Figure 7 G-MXene-PAA-Fe 3+ Schematic diagram of hydrogel compression and rebound;

[0055] Figure 8 Different ratios of MXene-PAA hydrogel and MXene-PAA-Fe 3+ Stress-strain curve of hydrogel; Figure 8-A is the stress-strain curve of MXene-PAA hydrogel with different ratios; Figure 8 -B is different proportions of MXene-PAA-Fe 3+ Stress-strain curve of hydrogel;

[0056] Fig. 9 G-MXene-PAA-Fe with different ratios 3+ Hydrogel stress-strain curve and elastic modulus of three hydrogels; Fig. 9 -A is different proportions of G-MXene-PAA-Fe 3+ Stress-strain curve of hydrogel; Fig. 9 -B is MXene-PAA hydrogel, MXene-PAA-Fe 3+ Hydrogel and G-MXene-PAA-Fe 3+ Elastic modulus diagram of hydrogel;

[0057] Fig.10 G-MXene-PAA-Fe with different MXene contents 3+ Stress-strain curve and elastic modulus diagram of hydrogel; Fig.10 -A is G-MXene-PAA-Fe with different MXene contents 3+ Stress-strain curve of hydrogel; Fig.10 -B is G-MXene-PAA-Fe with different MXene contents 3+ Elastic modulus diagram of hydrogel;

[0058] Fig.11 G-MXene-PAA-Fe with different ratios 3+ Stress-strain curve and toughness diagram of hydrogel; among them, Fig.11 -A is different proportions of G-MXene-PAA-Fe 3+ Stress-strain curve of hydrogel; Fig.11 -B is G-MXene-PAA-Fe with different ratios 3+ Toughness diagram of hydrogel;

[0059] Fig.12 G-MXene-PAA-Fe with different MXene contents 3+ Stress-strain curve and toughness diagram of hydrogel; among them, Fig.12 -A is G-MXene-PAA-Fe with different MXene contents 3+ Stress-strain curve of hydrogel; Fig.12 -B is G-MXene-PAA-Fe with different MXene contents 3+ Toughness diagram of hydrogel;

[0060] Fig.13 G-MXene-PAA-Fe 3+ Schematic diagram of hydrogel self-healing;

[0061] Fig.14 G-MXene-PAA-Fe 3+ A diagram of the hydrogel circuit connections;

[0062] Fig.15 G-MXene-PAA-Fe with different MXene contents 3+ Statistical graph of the electrical conductivity of the hydrogel;

[0063] Fig.16 MXene-PAA-Fe 3+ Hydrogel and G-MXene-PAA-Fe 3+ Graph of the resistance change of the hydrogel over 14 days;

[0064] Fig.17 G-MXene-PAA-Fe 3+ The sensitivity test results of hydrogel; Fig.17 -A is G-MXene-PAA-Fe 3+ Schematic diagram of the hydrogel before stretching; Fig.17 -B is G-MXene-PAA-Fe 3+ Schematic diagram of hydrogel stretching; Fig.17 -C is G-MXene-PAA-Fe 3+ Schematic diagram of the hydrogel after stretching; Fig.17 -D is G-MXene-PAA-Fe 3+ △R / R-ε fitting straight line diagram of hydrogel;

[0065] Fig.18 G-MXene-PAA-Fe when the finger is bent 0-90° 3+ A graph of the relative change in electrical resistance of the hydrogel samples;

[0066] Fig.19 G-MXene-PAA-Fe can bend fingers and wrists to a certain angle 3+ A graph of the real-time relative resistance change of the hydrogel; wherein, Fig.19 -A is the finger repeatedly bending at a certain angle G-MXene-PAA-Fe 3+ A plot of the real-time relative resistance change of the hydrogel; Fig.19 -B is the wrist repeatedly bent at a certain angle G-MXene-PAA-Fe 3+ Plot of the real-time relative resistance change of the hydrogel. DETAILED DESCRIPTION

[0067] The technical solution of the present invention will be further described clearly and completely in conjunction with specific embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0068] In the examples of the present invention, the main experimental reagents involved are shown in Table 1.

[0069] Table 1. Experimental reagents browsing table

[0070] Serial number name Specification Relative molecular weight 1 Acrylic acid (AA) 500mL / bottle 72.063 2 <![CDATA[TiAlC MAX phase ceramic composite material and preparation method thereof]]> 3 AlC 2 )MAX]]> 10g / bag 194.6 3 <![CDATA[Iron(III) chloride hexahydrate (FeCl 3 ·6H 2 O)]]> 500g / bottle 270.21 4 L-Ascorbic Acid (VC) 100g / bottle 176.12 5 Ammonium Persulfate (APS) 100g / bottle 228.20 6 Lithium Fluoride (LiF) 100g / bottle 25.94 7 Hydrochloric acid (HCl) 500mL / bottle 36.46

[0071] Table 2. List of experimental equipment

[0072]

[0073]

[0074] In the embodiments of the present invention, the preparation method of some reagents is as follows:

[0075] 1) Preparation of 9M HCl: At room temperature, measure 15 mL of concentrated hydrochloric acid (12M HCl), slowly inject 5 mL of deionized water along a glass rod, and stir with a magnetic stirrer until the solution is mixed evenly.

[0076] 2) Preparation of 1M HCl: At room temperature, measure 5 mL of concentrated hydrochloric acid (12M HCl), slowly inject 55 mL of deionized water along a glass rod, and stir with a magnetic stirrer until the solution is mixed evenly.

[0077] 3) Preparation of L-ascorbic acid solution: 2 g of L-ascorbic acid was dissolved in 20 mL of deionized water, and the solution was mixed uniformly under stirring with a magnetic stirrer to obtain an L-ascorbic acid solution with a concentration of 100 mg / mL.

[0078] 4) Preparation of ammonium persulfate solution: 0.25 g of ammonium persulfate powder was dissolved in 5 mL of deionized water, and the solution was mixed uniformly under stirring with a magnetic stirrer to obtain an APS solution with a concentration of 50 mg / mL.

[0079] 5) Preparation of ferric chloride solution: Dissolve 0.15 g of ferric chloride hexahydrate in 10 mL of deionized water and stir the solution with a magnetic stirrer until the solution is uniformly mixed to obtain a concentration of 15 mg / mL of FeCl 3 Solution.

[0080] In the embodiment of the present invention, MXene (Ti 3 C2 T X ) is synthesized by using LiF / HCl as etching solution and selective etching method. The preparation diagram is shown in Figure 1 As shown, the matrix Ti 3 AlC 2 The aluminum (Al) layer is removed, multiple layers of MXene clay are inserted, and single-layer MXene is obtained by ultrasonic stratification. The preparation method of MXene has been reported in the inventor's previous research, see the invention patent with publication number CN118755148A for details. The specific experimental steps are as follows:

[0081] (1) 1.0 g LiF was dissolved in 20 mL 9 M HCl solution at room temperature. After stirring for 20 min under magnetic stirring, 1.0 g Ti 3 AlC 2 Slowly add it into the above mixture solution, and then keep stirring at 35°C for 24 hours.

[0082] (2) After 24 h of reaction, the resultant was centrifuged at 3500 rpm for 5 minutes and the supernatant was discarded.

[0083] (3) Add 1 M hydrochloric acid and deionized water and centrifuge for multiple washings until the pH is greater than 5.

[0084] (4) The supernatant was discarded and water was added continuously. The solution was ultrasonicated in an ice bath under nitrogen for 1 h and centrifuged for 1 h to collect the supernatant, thereby preparing a monolayer MXene suspension (concentration of 10 mg / mL).

[0085] The present invention characterized the prepared MXene by means of Tyndall effect experiment, transmission electron microscopy, atomic force microscopy, scanning electron microscopy, and X-ray diffractometer. The results show that the MXene nanosheets prepared by the present invention have excellent dispersibility in water; the MXene nanosheets exhibit an ultra-thin but relatively smooth two-dimensional single-layer sheet structure, and the thickness of the single-layer two-dimensional MXene nanosheet is 3.3nm and the lateral size is 1.5μm; in addition, the XRD results show that the (002) peak of the single-layer MXene is stronger than the MAX phase peak, which indicates that the etching of the Al layer is relatively complete, indicating that the acid-etched MXene is successfully prepared. After etching, insertion, and further stratification, the obvious (002) peak moves from the typical 2θ angle of 9.7 of the parent MAX phase to a lower 2θ angle of about 6.5, which is a typical feature of MXene nanosheets.

[0086] Due to the ultra-thin thickness of MXene nanosheets and the subsequent introduction of Fe 3+ The synergistic effect of the two makes it have a large number of active sites and higher conductivity, which improves its activity.

[0087] Example 1. G-MXene-PAA-Fe 3+ Preparation method of self-healing conductive hydrogel

[0088] (1) Preparation of MXene: 1.0 g LiF was dissolved in 20 mL 9 M HCl solution at room temperature and magnetically stirred for 20 min to obtain an etching solution. 1.0 g Ti 3 AlC 2 Slowly add it to the etching solution, stir at 35°C for 24 hours, centrifuge at 3500 rpm for 5 minutes, and discard the supernatant; add 1M hydrochloric acid and deionized water respectively for multiple centrifugal washing until the pH of the supernatant is greater than 5; continue to add water after discarding the supernatant, ultrasonicate the solution in an ice bath under nitrogen conditions for 1 hour, centrifuge for 1 hour, collect the supernatant, and prepare a single-layer MXene suspension.

[0089] (2) Preparation of modified MXene: Take 2.5 mL of the monolayer MXene suspension obtained in step (1), add 17.5 mL of premixed L-ascorbic acid solution, ultrasonicate for 5 min, and shake on a shaker for 5 h to obtain 20 mL of G-MXene dispersion; the obtained G-MXene dispersion is freeze-dried and reconstituted with deionized water to a G-MXene dispersion with a concentration of 10 mg / mL.

[0090] (3) Preparation of G-MXene-PAA self-healing conductive hydrogel

[0091] Under the action of ultrasound, 500 μl of deionized water, 175 μl of G-MXene dispersion (concentration of 10 mg / mL), 250 μl of AA monomer and 50 μl of APS solution (concentration of 50 mg / mL) were added in sequence, and the G-MXene-PAA self-healing conductive hydrogel was obtained after uniform dispersion.

[0092] (4) G-MXene-PAA-Fe 3+ Preparation of self-healing conductive hydrogel

[0093] The G-MXene-PAA self-healing hydrogel obtained in step (3) was placed in a FeCl 3 The G-MXene-PAA-Fe 3+ Self-healing conductive hydrogel. 3 The amount of solution was calculated based on the ratio of 3 mol%-AA.

[0094] Example 2. Antioxidant modification of MXene

[0095] The MXene nanosheet dispersion was modified with L-ascorbic acid aqueous solution as an antioxidant to ensure a reducing environment. After 5 minutes of ultrasound, it was placed on a shaker and kept shaking for 5 hours to obtain a stable dispersion. In addition, the MXene colloid was diluted to the same concentration with deionized water, and a controlled dispersion was obtained after ultrasound. At this time, the concentrations of the two MXene dispersions were the same (1.25 mg / mL). According to the experimental situation, the two dispersions were diluted to the same concentration at room temperature and placed in a small glass bottle. After ultrasonic dispersion, the oxidation process was observed; on the other hand, the antioxidant modified monolayer G-MXene dispersion was freeze-dried and configured into a dispersion with the same concentration as the unmodified monolayer MXene dispersion. After ultrasound, they were stored together at low temperature for the preparation of hydrogels later. The operation steps are as follows:

[0096] ① Antioxidant modification group

[0097] For every 2.5 mL of the prepared MXene nanosheet dispersion, 17.5 mL of the premixed L-ascorbic acid solution was added, and after ultrasonication for 5 min, it was placed on a shaker and kept shaking for 5 h to obtain 20 mL of G-MXene dispersion.

[0098] ②Unmodified control group

[0099] For every 2.5 mL of prepared MXene nanosheet dispersion, 17.5 mL of deionized water was added to obtain 20 mL of MXene dispersion after sonication.

[0100] Example 3. Optimization of preparation conditions for self-healing conductive hydrogel

[0101] (1) Preparation of MXene-PAA self-healing conductive hydrogel and G-MXene-PAA self-healing conductive hydrogel

[0102] In the presence of MXene / G-MXene nanosheets and initiator APS, MXene-PAA / G-MXene-PAA nanocomposite hydrogels were prepared by in-situ free radical polymerization of AA monomers. The specific method is as follows: The antioxidant-modified G-MXene dispersion is freeze-dried to obtain a sponge-like powder solid. It is then dissolved in a certain amount of deionized water and ultrasonicated for 10 minutes to form a G-MXene dispersion with the same concentration as the unmodified MXene dispersion. Under the action of ultrasound, deionized water, MXene / G-MXene dispersion (10 mg / mL), AA monomer and APS solution (50 mg / mL) are added in sequence in different proportions to maintain uniform dispersion to obtain MXene-PAA self-healing conductive hydrogel and G-MXene-PAA self-healing conductive hydrogel.

[0103] This experiment explored the effects of different AA / APS ratios and different MXene amounts on the properties of the prepared hydrogels. The specific groups are shown in Tables 3 and 4.

[0104] Table 3. MXene-PAA hydrogel experimental group 1

[0105] AA:APS (volume ratio) AA (μl) MXene / G-MXene(μl) APS (μl) <![CDATA[H 2 O(μl)]]> 1:1 150 175 150 500 2:1 200 175 100 500 3:1 225 175 75 500 4:1 240 175 60 500 5:1 250 175 50 500 6:1 257 175 43 500 7:1 263 175 37 500 8:1 267 175 33 500

[0106] Table 4. MXene-PAA hydrogel experimental group 2

[0107]

[0108]

[0109] (2)MXene-PAA-Fe 3+ / G-MXene-PAA-Fe 3+ Preparation of self-healing conductive hydrogel

[0110] The prepared MXene-PAA / G-MXene-PAA self-healing hydrogel was placed in FeCl 3 Solution (15 mg / mL) was soaked for 30 min. 3 The amount of solution was calculated based on the ratio of 3 mol% -AA. Waiting for complete absorption and uniform coordination and cross-linking to form MXene-PAA-Fe 3+ / G-MXene-PAA-Fe 3+ Self-healing conductive hydrogel. Fe 3+ The uniform distribution of MXene nanosheets throughout the hydrogel is conducive to the uniform formation of Fe2+ bonds between the hydroxyl groups of MXene nanosheets and the carboxyl groups of PAA chains. 3+ Mediated coordination cross-linking further enhances its cross-linking mechanism, as shown in the schematic diagram Figure 2 shown.

[0111] Example 4. Characterization of MXene Antioxidant Modification

[0112] (1) Light visual observation

[0113] A certain concentration of G-MXene stable dispersion diluted with L-ascorbic acid aqueous solution was stored in a closed glass bottle for several days at room temperature. In addition, a certain concentration of MXene control dispersion diluted with deionized water was stored in a closed glass bottle under the same conditions for the same number of days. No degassing was performed before or during storage, so that the MXene dispersion solution was in contact with the headspace (air) of the bottle. During this period, the dispersion degree change and stability of the two dispersions were observed over a 22-day period.

[0114] 1) High concentration group

[0115] 5 mL of the prepared G-MXene stable dispersion with a concentration of 1.25 mg / mL and the MXene control dispersion were directly placed in a sealed glass bottle and stored for several days and observed.

[0116] 2) Low concentration group

[0117] The 1.25 mg / mL G-MXene stable dispersion and the MXene control dispersion were diluted to a concentration of 0.5 mg / mL, and then 5 mL was taken from each of them and placed in a sealed glass bottle for several days and observed.

[0118] result: Figure 3 Photos of MXene and G-MXene solutions at a concentration of 1.25 mg / mL collected at different times to study oxidative stability are shown. Both MXene and G-MXene dispersions appear black initially, but after two days of exposure in water, the MXene dispersion shows stratification, while the G-MXene dispersion does not change visually. This indicates that MXene nanosheets stored in water are more likely to aggregate and form precipitates, while the G-MXene solution on the right is uniform and stable under the same conditions, indicating that the G-MXene solution modified with L-ascorbic acid has a certain degree of stability. The experiment was repeated with lower concentrations of MXene and G-MXene dispersions (0.5 mg / mL) and the same observations were obtained, see for details. Fig. 9 .

[0119] Continuous observation shows that the MXene dispersion still shows stratification on the 5th to 8th day, while the G-MXene dispersion remains relatively stable and black. Afterwards, the stratified MXene dispersion is shaken evenly, and the solution will continue to show stratification over time. Figure 3 and Figure 4 It can be seen that no matter at high or low concentration, after the two dispersions were shaken evenly on the 14th day, the MXene dispersion in deionized water showed obvious agglomeration and the generation of granular substances. The dispersion status of the dispersion was more easily observed under sunlight. The G-MXene dispersion was still evenly distributed and black or dark green. The particles generated in the MXene dispersion are due to the titanium dioxide (TiO 2 ) and C show precipitation, indicating that the MXene dispersion has been severely oxidized at this time.

[0120] From then until the 22nd day, the MXene dispersion gradually turned gray and white, while the G-MXene dispersion was still relatively stable and black, indicating that the MXene nanosheets in the MXene dispersion degraded faster. It can be concluded that the single-layer MXene nanosheets treated with L-ascorbic acid became more stable in an oxygen-rich environment. It proves that MXene nanosheets can be protected from severe oxidation after being stored in an aqueous solution of sodium L-ascorbate for a long time, and the antioxidant modification of MXene in this experiment was successful.

[0121] (2) X-ray photoelectron spectroscopy (XPS)

[0122] Equal amounts of the prepared monolayer MXene dispersion and G-MXene dispersion were taken and vacuum filtered to form membranes. The filtered membranes were nitrogen-filled for 5 minutes at room temperature and sealed for storage until the membranes were evenly dried. Using an X-ray photoelectron spectrometer, the (Ti 3 AlC 2 )Surface chemical properties of MAX phase, MXene and G-MXene samples. XPS uses highly characteristic binding energy to qualitatively analyze the elemental composition of MAX phase and MXene materials, and observes the intensity of the corresponding peak of titanium dioxide in the nanosheets and the intensity of the Ti peak. This can determine whether the MXene modification is successful.

[0123] Results: XPS analysis of the samples showed that (Ti 3 AlC 2 ) There are obvious differences in the chemical compositions between MAX phase, MXene and G-MXene. Figure 5 -A, (Ti 3 AlC 2 )The XPS survey spectrum of the MAX phase shows a peak at 77.0 eV corresponding to Al, but it is below the detection limit of the spectra of MXene and G-MXene. This indicates that the HF treatment of the MAX powder removed most of the Al layer. The survey spectrum of MXene showed an F peak at 685.0 eV with an atomic content of 10.82%, which is due to the addition of fluorine during the HF etching process. After L-ascorbic acid treatment, the fluorine content dropped significantly to 8.66%. This shows that the L-ascorbic acid treatment significantly changed the surface chemistry of MXene, and the antioxidant treatment can remove a large amount of F in MXene.

[0124] The high-resolution spectrum of Ti2p is shown in Figure 5 -B, the fitting peak is divided into Ti + 、Ti 2+ 、Ti 3+ and Ti 4+For the prepared MXene nanosheets stored in deionized water and L-ascorbic acid solution, titanium dioxide (Ti 4+ ) contains relatively low atomic components in the Ti2p region. However, for samples stored in water, titanium dioxide (Ti 4+ ) contains a much higher atomic fraction, which can be confirmed by the high intensity peak around 462 eV, which is evidence of severe oxidation of MXene. 4+ 、Ti 3+ 、Ti 2+ and Ti + As expected, in the case of aging in water, we observe an increase in the relative composition of Ti species in the oxidized state (i.e., Ti 2+ and Ti 3+ Oxidized to Ti 4+ , Ti + Oxidized to Ti 2+ and Ti 3+ ). In the presence of L-ascorbic acid, Ti + To Ti 2+ / Ti 3+ The chemical state transformation of Ti is inhibited; 4+ Increases slowly over time.

[0125] (3) Conductivity test

[0126] At room temperature, the electrical conductivity of the above-mentioned MXene and G-MXene films was tested respectively by the four-probe method to verify whether the conductive performance of the modified G-MXene dispersion is better.

[0127] Results: The conductivity of the original monolayer MXene dispersion is 2.2 S·m -1 The conductivity of G-MXene dispersion modified with L-ascorbic acid can reach 7.7 S·m -1 This data further illustrates the success of the antioxidant modification of L-ascorbic acid, proving that it improves the stability of MXene dispersions, avoids oxidation in a short period of time, and retains the conductive properties of MXene materials to a certain extent.

[0128] Example 5. Gelation analysis of MXene-based self-healing conductive hydrogel

[0129] As shown in Example 3, the present invention synthesizes MXene-PAA hydrogel by in-situ free radical polymerization of acrylic acid (AA) monomer in the presence of MXene nanosheets and initiator ammonium persulfate (APS). MXene-PAA hydrogel is constructed using MXene nanosheets as multifunctional crosslinkers, on which there are a large number of polarized surface functional groups (-F, -OH, -O, etc.), which interact with the carboxyl groups on the PAA chain through hydrogen bonds. It should be pointed out here that due to the presence of low-valent Ti (II) and Ti (III) substances, MXene nanosheets have strong reducibility; therefore, the redox reaction between the reductive MXene nanosheets and the oxidative initiator (APS) greatly reduces the decomposition activation energy of APS and generates a large number of free radicals. At the same time, it also avoids the disadvantages of traditional AA free radical polymerization, such as high temperature, long time, and the need for corrosive and highly neurotoxic crosslinkers such as TEMED.

[0130] The gelling effect is as Figure 6 As shown in the figure, rapid gelation of MXene-PAA hydrogel can be observed at room temperature for about 10 minutes, while pure PAA hydrogel without MXene cannot be achieved at room temperature due to the lack of reduced MXene to assist in free radical generation. This indicates that MXene nanosheets replace the role of N,N,N',N'-tetramethylethylenediamine (TEMED) and catalyze APS to produce free radicals, which not only avoids long-term high-temperature free radical polymerization during the gelation process, but also gives it conductivity.

[0131] Example 6. Mechanical properties test of MXene-based self-healing conductive hydrogel

[0132] In order to test the strength of the prepared hydrogel, a mechanical universal testing machine was used to test the strength of the MXene-PAA / G-MXene-PAA hydrogel and the MXene-PAA-Fe 3+ / G-MXene-PAA-Fe 3+ The mechanical properties of the hydrogels were determined.

[0133] (1) Compression test

[0134] Compression tests were performed on the prepared hydrogel cylindrical samples (11 mm in diameter and 8.8 mm in height) and measured at a loading rate of 5 mm / min at ambient temperature. The compressive load (F) and displacement (x) were recorded.

[0135] The calculation formula for compressive stress is as follows:

[0136]

[0137] Among them, Load valueis the load value, unit N; r is the hydrogel radius, unit mm. Four parallel samples were tested in each group, and the average value of the test results was recorded.

[0138] The calculation formula for compressive strain is as follows:

[0139]

[0140] Among them, Position is displacement, unit is mm; h is hydrogel height, unit is mm. Four parallel samples were tested in each group, and the average value of the test results was recorded.

[0141] The elastic modulus of the hydrogel was estimated from the slope of the straight line fitted from 0% strain to 10% of the strain before fracture under the stress-strain curve.

[0142] The test results are as follows:

[0143] 1) The ratio of AA to APS: Figure 7 As shown, when the finger compresses G-MXene-PAA-Fe 3+ When the hydrogel was squeezed and deformed, it was not damaged; when the force applied by the finger was withdrawn, the hydrogel quickly rebounded from the compressed state and returned to its original state, indicating the excellent resilience of the hydrogel sample. The compressive mechanical properties of hydrogels are generally characterized by elastic modulus. The larger the elastic modulus of the hydrogel, the less likely the material is to deform. Figure 8 , Fig. 9 As can be seen from the figure, compared with MXene-PAA hydrogel, the introduction of Fe 3+ The MXene-PAA-Fe 3+ The elastic modulus of the hydrogel was improved, especially when AA:APS=5:1. 3+ The elastic modulus of the hydrogel (76.589 kPa) is 22.125 kPa higher than that of the MXene-PAA hydrogel (54.464 kPa). This is because the FeCl 3 The solution was then converted into a hydrogel with a large amount of uniformly coordinated cross-links, which improved the mechanical strength of the hydrogel.

[0144] It should be noted that the present invention uses G-MXene-PAA-Fe 3+ Hydrogel, with better performance than MXene-PAA and MXene-PAA-Fe 3+The higher elastic modulus of the hydrogel (96.046 kPa) proves that during the experimental process of preparing the hydrogel, waiting for demolding, and measuring the compression mechanics of the hydrogel, L-ascorbic acid avoided the oxidation of the MXene nanosheets as much as possible, so that its superior mechanical strengthening properties were retained as much as possible. As the ratio of AA to APS changed, the elastic modulus of the three hydrogels showed a trend of first increasing and then decreasing. Among them, 1:1, 7:1 and 8:1 were not tested for their compression mechanics due to the long gelation time. The longer the time, the higher the cost of hydrogel production, and it is more likely to suffer from long-term oxidation during the preparation process, resulting in a short service life. It can be seen from the elastic modulus diagram of the three hydrogels that when AA:APS=5:1, the elastic modulus of the prepared hydrogel is the highest, among which G-MXene-PAA-Fe 3+ The elastic modulus of the hydrogel can reach 96.046 kPa.

[0145] 2) The amount of MXene: Fig.10 As shown in Figure 2, when the content of G-MXene nanosheets increases to 175 μl, G-MXene-PAA-Fe 3+ The elastic modulus of the hydrogel increased and then gradually decreased. Specifically, the superior mechanical strengthening effect of G-MXene nanosheets lies in their larger specific surface area and more polarized functional groups, which effectively transfer the applied stress to more PAA chains. However, if there are too many G-MXene nanosheets, there will be no corresponding number of carboxyl groups on the PAA chains to interact with them, which will lead to incomplete gelation and reduced compression modulus.

[0146] (2) Tensile test

[0147] Tensile tests were performed on the prepared rectangular samples of hydrogel (30 mm in length, 10 mm in width, and 2 mm in height) and measured at a loading rate of 100 mm / min at ambient temperature with a measuring length of 15 mm between the grips. The tensile load (F) and displacement (x) were recorded.

[0148] The tensile stress is calculated as follows:

[0149] Stress (kPa) = 1000F ÷ S

[0150] Where F is the tensile load, in N; S is the cross-sectional area, in mm 2 .

[0151] The tensile strain is calculated as follows:

[0152] Strain = x ÷ l 0

[0153] Where x is the displacement, l 0is the measured length between the fixtures in mm.

[0154] The toughness (E) of the hydrogel was estimated from the area under the stress-strain curve from 0% strain to the fracture strain (ζβ) as follows:

[0155]

[0156] The results are as follows:

[0157] 1) Ratio of AA to APS: The tensile mechanical properties of hydrogels are generally characterized by toughness and elongation at break. Toughness is an important mechanical property index to measure the toughness of materials. The larger its value, the smaller the elastic deformation of the material under the same stress conditions. Fig.11 As shown, when AA:APS=5:1, G-MXene-PAA-Fe 3+ The hydrogel has the highest toughness, which can reach 1443.756 kPa, and the elongation at break is 926.7%.

[0158] 2) Amount of MXene:

[0159] like Fig.12 As shown in Figure 2, when the content of G-MXene nanosheets increases to 175 μl, G-MXene-PAA-Fe 3+ The toughness of the hydrogel increased and then gradually decreased. Specifically, the superior mechanical strengthening effect of G-MXene nanosheets lies in their larger specific surface area and more polarized functional groups, which effectively transfer the applied stress to more PAA chains. As with the compressive mechanical properties, too many G-MXene nanosheets will not have a corresponding number of carboxyl groups on the PAA chains to interact with them, which will lead to incomplete gelation, and the tensile mechanical properties will also be reduced accordingly.

[0160] The above results show that when the amount of G-MXene is 175 μL, the amount of acrylic acid monomer is 250 μL, the amount of ammonium persulfate solution is 50 μL, and H 2 The amount of H O was 500 μL (i.e., G-MXene: acrylic acid monomer: ammonium persulfate solution: H 2 O=3.5:5:1:10) 3+ Hydrogel, with the best mechanical properties.

[0161] Example 7. Self-healing performance test of MXene-based self-healing conductive hydrogel

[0162] The G-MXene-PAA-Fe prepared in this experiment 3+ The hydrogel has multiple hydrogen bonds and Fe 3+The self-healing property of the metal coordination bond of the coordination center. Due to the combined effect of multiple hydrogen bonds and metal coordination bonds, the hydrogel has excellent self-healing properties. At room temperature, the hydrogel sample (AA:APS=5:1, MXene amount is 175μl) is evenly cut into two equal parts, and then the broken surfaces of the two parts are seamlessly placed together, and the self-healing is observed without the influence of other external forces. Then, under the same test conditions, the self-healed hydrogel is subjected to a mechanical compression test. At the end of the test, the compressive mechanical properties of the self-healing hydrogel are compared with those of the original hydrogel to verify the excellence of the hydrogel's self-healing properties and calculate its self-healing rate.

[0163] The calculation formula of self-healing rate is as follows:

[0164]

[0165] Among them, E 1 is the elastic modulus of the hydrogel after self-healing, E 0 is the elastic modulus of the original hydrogel.

[0166] Results: The G-MXene-PAA-Fe prepared in the present invention 3+ Due to the combined effects of multiple hydrogen bonds and metal coordination bonds, hydrogels have excellent self-healing properties. Fig.13 As shown, G-MXene-PAA-Fe 3+ The hydrogel sample healed quickly within 15 minutes, and no obvious gaps were seen. The hydrogel could be suspended in the air by clamping one side with tweezers, indicating that the hydrogel had basically healed. After 12 hours, the hydrogel had completely healed, and the two ends of the hydrogel could be pulled, and it could not be torn apart by applying force with tweezers. By testing the mechanical properties of the healed hydrogel, its elastic modulus was found to be 83.960 kPa, which was found to be slightly different from the elastic modulus of the hydrogel before cutting (89.125 kPa), indicating that the G-MXene-PAA-Fe prepared by the present invention 3+ The hydrogel has excellent self-healing performance. The self-healing rate of the self-healing hydrogel is calculated to be 94.2%.

[0167] Example 8. Conductive performance test of MXene-based self-healing conductive hydrogel

[0168] (1) Dynamic hydrogel-based circuit testing

[0169] Power, switch, G-MXene-PAA-Fe 3+The hydrogel (AA:APS=5:1, MXene volume 175μl) and the red light-emitting diode (LED) bulb were connected into a closed loop with wires to see if the LED bulb could be successfully lit under an applied voltage. The hydrogel was cut in half, the circuit was disconnected, and the fractured surfaces of the hydrogel were brought together again to observe the brightness of the LED bulb.

[0170] Results: Fig.14 -A, power supply, switch, G-MXene-PAA-Fe 3+ The hydrogel (AA:APS=5:1, MXene content 175μl) and the red light-emitting diode (LED) bulb were connected into a closed loop with wires, and the LED bulb was successfully lit under an applied voltage. When the hydrogel was cut in half, the circuit was disconnected and the bulb went out. Fig.14 -B; put the broken surfaces of the hydrogel together again, and the brightness of the LED bulb was not much different from before. Fig.14 -C. When the hydrogel conductor was cut, the bulb dimmed, but once the two separated hydrogel parts were reconnected, the LED bulb immediately emitted bright light, indicating that the conductive hydrogel was immediately electrically restored. The rapid electrical recovery is due to the many reversible interactions between the polarizable surface functional groups (-F, -OH, =O, etc.), such as MXene nanosheets, PAA and Fe 3+ In addition, a large number of dynamic interactions make G-MXene-PAA-Fe 3+ The hydrogel has excellent self-healing ability in terms of mechanical properties. Therefore, the obtained hydrogel has almost instant mechanical and electrical self-healing ability, and has broad application prospects as a wearable smart strain sensor in reliable and flexible electronic devices.

[0171] (2) Conductivity test

[0172] Measurement of G-MXene-PAA-Fe with different MXene amounts by four-probe method 3+ Electrical conductivity of the hydrogel. The diameter of the cylindrical hydrogel sample is 11 mm and the height is 8.8 mm.

[0173] Results: Fig.15 As shown, as the amount of MXene gradually increases, the conductivity of the hydrogel sample also gradually increases, but when the amount of MXene is 205μl, the conductivity decreases. This may be because the hydrogel gelation effect is not good, resulting in an uneven surface of the hydrogel sample and inaccurate conductivity test.

[0174] (3) Resistance change of hydrogel after 14 days

[0175] MXene-PAA-Fe 3+Hydrogel and G-MXene-PAA-Fe 3+ The resistance change of the hydrogel (AA:APS=5:1, MXene amount is 175μl) stored in a normal environment for 14 days was compared to verify whether the antioxidant modification of MXene successfully improved the stability of the hydrogel.

[0176] Results: Fig.16 As shown, with MXene-PAA-Fe 3+ Compared with hydrogel, G-MXene-PAA-Fe 3+ The resistance change of the hydrogel was relatively weak within 14 days. 3+ The resistance change of the hydrogel is G-MXene-PAA-Fe 3+ The hydrogel resistance changed by 3.14 times; by the 14th day, MXene-PAA-Fe 3+ The hydrogel resistance changes by 16.1%, G-MXene-PAA-Fe 3+ The resistance of the hydrogel changed by 3.5%, and the change ratio reached 4.6 times. This result shows that L-ascorbic acid has a good antioxidant modification effect and can keep the MXene-based hydrogel in a certain electrical stability for a long time.

[0177] Example 9. Sensing test of MXene-based self-healing conductive hydrogel

[0178] (1) Sensitivity

[0179] In the strain sensing experiment, a rectangular G-MXene-PAA-Fe with a thickness of 3 mm, a length of 30 mm, and a width of 5 mm and a cylindrical G-MXene-PAA-Fe with a diameter of 11 mm and a height of 8.8 mm were prepared. 3+ Hydrogel (AA:APS=5:1, MXene amount is 175μl) sample. G-MXene-PAA-Fe 3+ Hydrogels are used to evaluate their electrical sensitivity as strain sensors. The strain sensitivity of hydrogels is quantitatively evaluated by the measurement factor (GF). The larger the value of the measurement factor GF, the higher the sensitivity. The GF calculation formula is as follows:

[0180]

[0181] Where ΔR is the change in resistance, ΔR = RR 0 ; R 0 is the initial resistance of the hydrogel, R is the resistance at a certain moment during the stretching / compression process, and ε is the strain at that moment.

[0182] Results: Fig.17 -A. Fig.17-B. Fig.17 -C, the resistance of the hydrogel sample changes with different strains during the tensile strain process. Then, a line graph is drawn with strain (%) as the horizontal axis and △R / R as the vertical axis, and a straight line is fitted. The slope is the measurement factor GF. Fig.17 -D, G-MXene-PAA-Fe 3+ The sensitivity of the self-healing hydrogel is 3.68.

[0183] (2) Using G-MXene-PAA-Fe 3+ The hydrogel (AA:APS=5:1, MXene amount of 175μl) was simulated as a wearable electronic sensor to monitor finger bending movement. The hydrogel was cut into rectangular samples with a thickness of 2mm, a length of 20mm, and a width of 5mm. The G-MXene-PAA-Fe 3+ Changes in hydrogel electrical resistance.

[0184] Results: Fig.18 As shown in the real-time recording, as the finger bending angle changes from 0 to 90°, G-MXene-PAA-Fe 3+ The relative change in resistance of the hydrogel sample. The hydrogel sensor can accurately detect the different bending angles of the finger in real time, and immediately return to the initial resistance once the finger returns to its original unbent state.

[0185] (3) Repeat the finger and wrist bending process to continuously measure G-MXene-PAA-Fe 3+ The change in hydrogel resistance further verifies the stability of the hydrogel.

[0186] Results: Fig.19 As shown in the figure, the real-time relative resistance change of the sensor when bending the finger and wrist respectively. During the repeated bending process, the hydrogel sensor can always output the relative resistance change of the process relatively stably, further verifying the G-MXene-PAA-Fe 3+ The stability of the hydrogel for sensor application, therefore, the obtained hydrogel has application prospects as a wearable smart strain sensor.

Claims

1. Preparation of G-MXene-PAA-Fe 3+ The composition of the self-healing conductive hydrogel is characterized in that The composition comprises the following components: modified G-MXene, acrylic acid and FeCl3; the volume ratio of the modified G-MXene to the acrylic acid is 170-180:230-270; the volume of the FeCl3 is 2-4 mol% of the acrylic acid monomer.

2. The composition according to claim 1, characterized in that The MXene is modified by an antioxidant to obtain the modified G-MXene; the volume ratio of the MXene to the antioxidant is 1:5-10; and the antioxidant is L-ascorbic acid.

3. The composition according to claim 1, characterized in that The composition further comprises an initiator; the volume ratio of the acrylic acid to the initiator is 4-6:1; and the initiator is ammonium persulfate.

4. Preparation of G-MXene-PAA-Fe based on the composition described in claim 1 3+ A method for self-healing a conductive hydrogel, characterized in that The steps include: S1: under the action of ultrasound, deionized water, modified G-MXene, acrylic acid monomer and ammonium persulfate solution are added in sequence to uniformly disperse to obtain G-MXene-PAA hydrogel; the volume ratio of the deionized water, the modified G-MXene, the acrylic acid monomer and the ammonium persulfate solution is 500:170-180:230-270:50; S2: The G-MXene-PAA hydrogel obtained in S1 was immersed in a FeCl3 solution to obtain G-MXene-PAA-Fe 3+ Self-healing conductive hydrogels.

5. The method according to claim 4, characterized in that In S1, the volume ratio of the deionized water, the modified G-MXene, the acrylic acid monomer and the ammonium persulfate solution is 10:3.5:5:

1.

6. The method according to claim 4, characterized in that In S2, the volume of the FeCl3 solution is 2 to 4 mol% of the acrylic acid monomer.

7. The method according to claim 4, characterized in that The preparation method of the modified G-MXene is as follows: (1) Ti3AlC2 was added to LiF / HCl etching solution to synthesize MXene by selective etching; (2) Using an antioxidant to modify the MXene obtained in step (1) to obtain the modified G-MXene.

8. The method according to claim 7, characterized in that In step (2), the volume ratio of the MXene to the antioxidant is 1:5-10; and the antioxidant is L-ascorbic acid.

9. G-MXene-PAA-Fe prepared by the method described in any one of claims 4 to 8 3+ Self-healing conductive hydrogels.

10. The composition according to any one of claims 1 to 3 and / or the G-MXene-PAA-Fe according to claim 9 3+ Application of self-healing conductive hydrogels in the preparation of wearable flexible sensors.

Citation Information

Patent Citations

  • Self-repairing conductive hydrogel based on modified MXene as well as preparation method and application of self-repairing conductive hydrogel

    CN118755148A

  • Preparation method of antioxidant Mo2C-TA nanosheet and application of antioxidant Mo2C-TA nanosheet in diabetes wound healing and pulmonary fibrosis treatment

    CN117959331A

  • Conductive Hydrogel-Based Wearable Health Monitors

    US20230397870A1

Cited By

  • Ultrafiltration membrane for sewage treatment and preparation method thereof

    CN121401877A